CNS penetration of ART in HIV-infected children. (8th November 2017) - Van den Hof, Malon; Blokhuis, Charlotte; Cohen, Sophie; Scherpbier, Henriette J; Wit, Ferdinand W N M; Pistorius, M C M; Kootstra, Neeltje A; Teunissen, Charlotte E; Mathot, Ron A A; Pajkrt, Dasja
Abstract: Background: Paediatric data on CNS penetration of antiretroviral drugs are scarce. Objectives: To evaluate CNS penetration of antiretroviral drugs in HIV-infected children and explore associations with neurocognitive function. Patients and methods: Antiretroviral drug levels were measured in paired CSF and blood samples of clinically stable HIV-infected children between 8 and 18 years old on long-term combined ART. Plasma drug concentrations were corrected for protein binding. We evaluated CNS penetration using CSF/plasma ratios and compared CSF concentrations with the IC50 as a surrogate marker for effectiveness. Blood–brain barrier permeability was assessed for possible confounding. Associations with neurocognitive function were explored using linear regression analysis. Results: Median CSF/plasma ratios (IQR) were: lopinavir 0.059 (0.024–0.157, n  =   7), efavirenz 0.681 (0.555–0.819, n  =   12), tenofovir 0.021 (0.020–0.024, n  = 4), lamivudine 0.464 (0.331–0.607, n  =   17), emtricitabine 0.365 (0.343–0.435, n  =   3), nevirapine 1.203 ( n  =   1), zidovudine 0.718 (0.711–1.227, n  =   5) and abacavir 1.344 (0.670–2.450, n  =   10). CSF concentrations were below the IC50 for tenofovir (100%), emtricitabine (100%), abacavir (50%) and zidovudine (17%). Lamivudine, lopinavir, efavirenz and nevirapine concentrations were all above the IC50 . All participants were virologically suppressed in blood and CSF. CSF drug concentrations were not associated with blood–brain barrier permeability or neurocognitive function. Conclusions: We showed adequate CSF concentrations of lamivudine, lopinavir, efavirenz and nevirapine, and potential suboptimal CSF concentrations of tenofovir, abacavir and emtricitabine in long-term treated HIV-infected children. None the less, the use of combined antiretroviral drugs led to adequate viral suppression.